Is the 'Developing World' Changing? A Dynamic and Multidimensional Taxonomy of Developing Countries. Issue 5 (November 2016) - Tezanos Vázquez, Sergio; Sumner, Andy
Abstract Existing classifications of developing countries have been based on – or dominated by – income per capita. Even those deemed to be 'alternatives' to the income classification include income per capita as a main component. This article proposes an alternative approach to classifying countries based on cluster analysis that allows us to identify the key development characteristics of each cluster of countries. We build five clusters of developing countries and consider changes over time since the late 1990s. We find that there is neither a simple 'linear representation of development levels' (from low- to high- development countries) nor a 'linear dynamic of development' (as if groups were 'immutable' and countries were just trying to accommodate themselves to the 'established' groups), which implies that the dominant international classification needs review. Instead our multidimensional and dynamic taxonomy offers a more nuanced understanding of the diversity of challenges of developing countries and their evolution over time. Abstract Les classifications existantes des pays en développement ont été fondées sur – ou dominées par – le revenu par habitant. Même celles qui sont considérées comme des « alternatives» à la classification du revenu par habitant incluent le revenu par habitant comme une composante qui est fortement pondérée. Cet article propose une approche alternative à la classification des pays, basée sur l'analyse de cluster qui nous permet d'identifier les caractéristiques clés du développement de chaque groupe de pays. Nous construisons cinq groupes de pays en développement et nous considérons les changements au fil du temps depuis la fin des années 1990 au sein des groupes eux-mêmes, au sein des pays de chaque groupe et dans le monde en développement dans son ensemble.